A Child Character’s Development in R.J. Palacio’s Children’s Realistic Fiction Novel Wonder - Rindra Nuriza (Universitas Pendidikan Indonesia (UPI), 2014)
Besides entertaining, children’s literature is expected to stimulate children’s understanding about particular values in real life and contributes to their development and needs. Due to this importance, many stories for children are delivered through realistic fiction. This paper thus aimed at investigating a child character’s development in realistic fiction and identifying the contributions of focalization to the main character’s development by using Bal’s narratology (2009) as the main framework. To analyze data in the form of written texts, qualitative method with descriptive analysis was applied. The results showed that the main character developed through four key narrative events and different focalization. Both were examined to explicate the dynamic changes in his personalities and attitudes. The development was also contributed by the six characters’ focalization which mostly revealed the shifts of direct and indirect speech, and the cognitive and perceptual views. This means that R.J. Palacio’s Wonder is successful in portraying a realistic fiction picture of a deformed child. In consequence, it shows that multiple focalization opens horizon to different perspectives which is important in children’s literature (Nikolajeva, 2002).Keywords: Children’s Literature, Character Development, NarratologyNews tends to be manipulated by some people to control over other people because news shapes publics opinions. Nowadays people can share news content easily in internet because internet becomes space where people can connect, communicate, and share everything easily. In line with that, this present research examined the representation of Muhammad Daming Sunusi concerning his controversial statement “women enjoy being raped” as evidenced in Indonesian Online Newspapers by using Sociosemantic approach from van Leeuwen (2008). This research employed descriptive qualitative method to describe the representation and its significance. The collected data were 6 online articles taken from Detik, Kompas, and Tribunnews. The data were analyzed in the unit of words, phrases, and sentences to reveal the representation of Muhammad Daming Sunusi concerning his controversial statement. This research disclosed that, according to the text, Muhammad Daming Sunusi was represented as the one who should be responsible of his statement and he was also represented in a negative way since his case was considered as an insult to the rape victims. Hence, by sociosemantic and context analysis, the research revealed that Detik, Kompas, and Tribunnews had the same pattern and thought in representing Muhammad Daming Sunusi.